Вскрытие медеплавильных шлаков хлоридом аммония; Известия вузов. Цветная металлургия; № 5 - Дьяченко А. Н. Александр Николаевич; Крайденко Р. И. Роман Иванович; Чегринцев С. Н. Сергей Николаевич; Порывай Е. Б. (2013, 2013)
Заглавие с экрана